Belimumab for Immune-Mediated Necrotizing Myopathy Associated With Anti-SRP Antibodies: A Case Report and Retrospective Review of Patients Treated With Anti-B-Cell Therapy in a Single Center and Literature - Cui, Bei-Bei; Tian, Yun-Ru; Ma, Xin-Yue; Yin, Geng; Xie, Qibing (Frontiers in Immunology, 2021)
Background: Immune-mediated necrotizing myopathy (IMNM) is characterized by positive antibodies against signal recognition particle (SRP) or 3-hydroxy-3-methylglutaryl-coA-reductase (HMGCR), markedly elevated creatine kinase, histologically scattered necrotic muscle fibers undergoing myophagocytosis and scant inflammation localized to necrotic fibers. Poor clinical responses to conventional therapies and relapses commonly occurred in severe cases. Anti-B cell therapies have been performed in some refractory cases. Methods: Characteristics of a patient with IMNM associated with anti-SRP antibodies included physical examination, laboratory tests, and disease activity assessment. Conventional therapy, belimumab treatment schedule and follow-up data was recorded. Medical records of IMNM patients in our department were reviewed from September 2014 to June 2021 to evaluate efficacy and safety of anti-B cell therapies for anti-SRP IMNM . To further exploration, a literature review of patients with anti-SRP IMNM treated with anti-B cell therapies was performed. Results: We described a 47 years old woman with IMNM associated with anti-SRP antibodies who relapsed twice after conventional therapy, showing good response and tolerance to belimumab in 28 weeks follow-up. In the review, three patients from our department were treated with RTX. Two of three patients’ condition was rapidly improved after treatment. In the literature review, 23 patients were included. All of the patients were taken RTX as anti-B cell drug. Conclusion: Anti-B cell therapies might be helpful for patients with refractory IMNM associated with anti-SRP antibodies. Belimumab, as a new anti-B cell agent, showed its efficacy and safety in IMNM treatment.